Pengaruh Kecerdasan Emosional dan Pemahaman Kode Etik Akuntan Terhadap Sensitivitas Etis Mahasiswa Akuntansi Politeknik Negeri Batam - Dede Medianty S; Hajan Hidayat (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
This study aims to examine the impact of Emotional Intelligence and Comprehension of the Accountant's Code of Ethics on the Ethical Sensitivity of Accounting Students. The sample of this research is active students from the accounting study program at the Batam State Polytechnic class of 2018-2019 who have received ethical learning through professional ethics courses totaling 90 students. This research includes the type of survey research, with the research instrument is a questionnaire. The data analysis technique used is multiple linear analysis. The results of the study prove that: Emotional Intelligence has a positive influence on the ethical sensitivity of accounting students at the Batam State Polytechnic, Understanding the Accountant Code of Ethics has a positive influence on the ethical sensitivity of accounting students at the Batam State Polytechnic, Emotional Intelligence and Comprehension of the Accountant Code of Ethics have a positive influence simultaneously on the ethical sensitivity of accounting students at the Batam State Polytechnic